Pengaruh Citra Destinasi Terhadap Niat Berkunjung Kembali di Pantai Samudera Baru Karawang - Fajri Hakim; Irena Novarlia; Dally Nur Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tourism for most individuals is an unavoidable need, entertainment needs ranging from traveling to various tourist attractions, as well as culinary delights in various regions in the province, one of which is West Java province which has 290 tourist attractions spread across 27 cities. and district. Of the many tourist attractions in the province of West Java, one of them is the city and district of Karawang which has diverse tourism potential such as: natural, artificial, cultural, religious and historical tourism. One of the natural attractions in Karawang Regency is the new ocean beach. Destination image is a person's perception of products, objects and behavior, as well as events that are driven by beliefs, feelings and a series of goals for a particular destination or tourist trip. Destination image is able to influence tourists. with the intention of visiting again. The aim of this research is to determine the influence of destination image on intention to revisit Karawang's new ocean beach. This research uses descriptive and verification analysis with a quantitative approach. Research data was taken directly using a questionnaire from 100 respondents from New Ocean Beach tourists using a purposive sampling technique and then analyzed using SPSS. The research results show that the image of the destination has a positive and significant influence, namely 62%, on the intention to visit again. The better the image of the dining destination, the more tourist visits to the new ocean beach Karawang will increase. It is hoped that future researchers can add other variables that can influence the intention to visit again, such as facility variables, destination quality and tourist attractions. Apart from that, future research will use qualitative methods to get more varied results.